2006
DOI: 10.1152/ajprenal.00281.2004
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate induces complex redox alterations in mesangial cells

Abstract: Indoxyl sulfate is a protein metabolite that is concentrated in the serum of patients with chronic renal insufficiency. It also is a uremic toxin that has been implicated in the progression of chronic renal disease in rodent models. We have shown previously that mesangial cell redox status is related to activation of mitogen-activated protein kinases and cell proliferation, which are factors related to glomerular damage. We used three methods to examine the ability of indoxyl sulfate to alter mesangial cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 36 publications
(56 reference statements)
3
96
0
2
Order By: Relevance
“…Previous studies of the induction of ROS by IS were limited to the use of renal tubule cells (OK cells) and mesanginal cells, but no findings in intravascular cell lines have been reported (10,14). However, our results clearly show that IS also induce ROS production in HUVECs to a remarkably extent and this was largely inhibited by AST-120 pretreatment.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Previous studies of the induction of ROS by IS were limited to the use of renal tubule cells (OK cells) and mesanginal cells, but no findings in intravascular cell lines have been reported (10,14). However, our results clearly show that IS also induce ROS production in HUVECs to a remarkably extent and this was largely inhibited by AST-120 pretreatment.…”
Section: Discussionsupporting
confidence: 49%
“…We previously reported that IS was taken up by proximal tubular cells by organic anion transporters (Oat1, Oat3) and Motojima et al demonstrated that such cellular uptake causes proximal tubular injury (28,29). In addition, Gelasco et al found that IS stimulates the production of intracellular and extracellular ROS in rat mesanginal cells, through a pathway that most likely involves NADPH oxidase or NADPH like oxidase (14). However, determining the molecular mechanism by which IS induces the ROS production in the endothelial cells will require further in vitro studies, which are now underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, other groups reported that indoxyl sulfate promoted oxidative stress in endothelial cells and the kidney. [16][17][18][19] These results strongly suggest the involvement of uremic toxins in the development of atherosclerosis. AST-120 has been known to decrease serum levels of indoxyl sulfate significantly in CKD rat models and also in CKD patients.…”
Section: Discussionmentioning
confidence: 66%
“…La coloración púrpura puede aparecer desde horas hasta días posteriores a la colocación del catéter urinario y se hace más intensa a medida que pasa el tiempo, sin realizar un recambio oportuno de la bolsa colectora de orina. Es interesante observar que la orina no es púrpura al ser colocada en otro recipiente estéril 9 .…”
Section: Discussionunclassified